LEMBAGA PERKREDITAN DESA SEBAGAI KEWIRAUSAHAAN BERBASIS KERAKYATAN PADA DESA PEKRAMAN DI BALI (SUATU PERSPEKTIF LPD SEBAGAI PENUNJANGPEMBANGUNAN DESAWISATA BERKELANJUTAN) - Luh Kompiang Sari (Maha Widya Bhuwana: Jurnal Pendidikan, Agama dan Budaya, 2021)
The Provincial Government of Bali in developing quality human resources with integrity, professional, moral and has an identity based on the values of local wisdom implied in the Vision "Nangun Sad kerti Loka Bali". The implementation of all these stakeholders is incorporated in the form of an organization, namely the pekraman village. The pekraman village is a regional legal community unit in the Province of Bali which has a unified form of tradition and social manners for Hindu people from generation to generation in the three heavenly ties, which has a certain area. Own property rights or rights of household servants on the basis of kinship, mutual cooperation and togetherness principles. Various ways have been made in an effort to increase equity and welfare of the community. One of them is building community-based entrepreneurship, namely the Community Credit Institution (LPD). So the LPD is a non-bank financial institution, whose management is under the auspices of each pekraman village and is the guidance of the Bali Provincial Government. The purpose of forming an LPD is to help industrial and tourism activities become steady and sustainable. Thus, it can make the pekraman village a sustainable tourism village